Neoliberalism as a Prevailing Force on the Conditions of Teacher Education in Canada (Alberta Journal of Educational Research, 2019)
This paper examines the impact of neoliberalist macro-policy and culture on the conditions and practice of teacher education in Canada. The origins and central features of neoliberalism are unpacked to show how the centrality of the nation state of liberalism has been replaced under neoliberalism by the distorted myth of a minimalist state that in reality reshapes social institutions along market lines and uses state regulation machinery to ensure that the market model is dominant to the point of diminishing the idea of the “public good.” This has made the world very unstable, leading to civil strife, political violence and an ongoing diasporization associated with trans-national migration. Within this unstable world, higher education and teacher education in Canada take place. I then turn to examining the impact of neoliberalist policy on higher education as a foreground to examining the impact of neoliberalist policy conditions on Canadian teacher education. Three themes are extrapolated to demonstrate this impact—the conflicted challenge between institutional legitimacy and professional identity that working in a higher education context presents to Canadian teacher educators; some unresolved issues of accessibility and accountability in Canadian teacher education programs; and the ways in which a commitment to social justice with its emphasis on inclusion, diversity, and multiculturalism that Canadian teacher educators name as important are frustrated and sometimes impeded. My thesis is that neoliberalism is using audit conditions of accountability to re-frame teachers’ work as an occupational relationship. My claim is that if economic rationalist accountability ends up trumping professional judgment, then teaching will potentially lose its professional status. And, if that happens, there will likely be no place for university teacher education.Cet article porte sur l’impact de la macro-politique et la culture néolibérales sur les conditions et la pratique de la formation des enseignants au Canada. Les origines et les caractéristiques essentielles du néolibéralisme sont exposées afin de démontrer dans quelle mesure la centralité de l’état nation du libéralisme a été remplacée sous le néolibéralisme par le mythe déformé d’un état minimaliste qui, en réalité, remanie les institutions sociales selon les principes de la liberté du marché et utilise l’appareil de la réglementation étatique pour assurer que le modèle du marché domine jusqu’au point de diminuer l’idée du « bien public ». Le résultat en est un monde très instable caractérisé par des troubles civils, de la violence politique et des déplacements constants liés à la migration transnationale. C’est dans ce contexte instable que se déroulent les études supérieures et la formation des enseignants au Canada. L’examen de l’impact de la politique néolibérale sur les études supérieures sert de toile de fond pour l’étude de l’impact des politiques néolibérales sur la formation des enseignants au Canada. Trois thèmes démontrent bien cet impact : le défi que pose, pour les formateurs d’enseignants au Canada œuvrant dans les milieux des études supérieures, le conflit entre la légitimité institutionnelle et l’identité professionnelle; des problèmes non résolus dans les programmes de formation des enseignants et portant sur l’accessibilité et la responsabilité; et les entraves qui se dressent parfois devant un engagement envers la justice sociale visant l’inclusion, la diversité et le multiculturalisme, éléments que les formateurs d’enseignants indiquent comme étant importants. Ma thèse propose que le néolibéralisme emploie des conditions de vérification pour reformuler le travail des enseignants comme une relation professionnelle. J’affirme que si les notions économiques et rationalistes de la responsabilité finissent par l’emporter sur le jugement professionnel, l’enseignement pourrait perdre son statut professionnel. Si cela devait se produire, il est probable que la formation universitaire des enseignants n’aurait plus sa place au Canada.Mots clés : néolibéralisme, travail des enseignants, formation des enseignants, intellectuel public